News Releases and Public Service Announcements - Ricky Telg (EDIS)
You may be called upon to write a news release or public service announcements about your organization’s activities, interesting news, or important events. This 2-page fact sheet provides tips about how to write news releases and PSAs. Written by Ricky Telg and published by the UF Department of Agricultural Education and Communication, August 2011. (Image: Tom Nordlie, IFAS news writer, works on a story. Photo by Tara Piasio)